Thermal–Hydraulic Characteristics of Novel Configurations of Wavy Channel: Nanofluid as Working Fluid. Issue 16 (2nd November 2017) - Khoshvaght-Aliabadi, Morteza
ABSTRACT: In the present study, thermal-hydraulic specifications of the wavy channel with variable wave lengths are investigated numerically in the presence of Al2 O3 –water nanofluid. The nanofluid concentration and Reynolds number range are 0–9% vol. and 200–1400, respectively. Four nonuniform arrangements of the wave length, including low to high, high to low, low to high to low, and high to low to high, are evaluated in comparison with the uniform one. Furthermore, the effects of the channel height and wave amplitude on the performance of the wavy channels are examined. The results show that the wave length variations have significant effects on the performance of the wavy channel. At the studied ranges, the wavy channel with the low to high wave length variations depicts the best performance, and the channel with the high to low to high comes in the second. Also, the nanofluids with the higher concentration propose the greater values of Nusselt number and friction factor. Finally, correlations are developed for both the uniform and the nonuniform wavy channels as function of Reynolds number, Prandtl number, nanofluid concentration, and geometrical parameters.